Epigenetic mechanisms of Müller glial reprogramming mediating retinal regeneration - Si, Tian-En; Li, Zhixiao; Zhang, Jingjing; Su, Songxue; Liu, Yupeng; Chen, Shiyue; Peng, Guang-Hua; Cao, Jing; Zang, Weidong (Frontiers in Cell and Developmental Biology, 2023)
Retinal degenerative diseases, characterized by retinal neuronal death and severe vision loss, affect millions of people worldwide. One of the most promising treatment methods for retinal degenerative diseases is to reprogram non-neuronal cells into stem or progenitor cells, which then have the potential to re-differentiate to replace the dead neurons, thereby promoting retinal regeneration. Müller glia are the major glial cell type and play an important regulatory role in retinal metabolism and retinal cell regeneration. Müller glia can serve as a source of neurogenic progenitor cells in organisms with the ability to regenerate the nervous system. Current evidence points toward the reprogramming process of Müller glia, involving changes in the expression of pluripotent factors and other key signaling molecules that may be regulated by epigenetic mechanisms. This review summarizes recent knowledge of epigenetic modifications involved in the reprogramming process of Müller glia and the subsequent changes to gene expression and the outcomes. In living organisms, epigenetic mechanisms mainly include DNA methylation, histone modification, and microRNA–mediated miRNA degradation, all of which play a crucial role in the reprogramming process of Müller glia. The information presented in this review will improve the understanding of the mechanisms underlying the Müller glial reprogramming process and provide a research basis for the development of Müller glial reprogramming therapy for retinal degenerative diseases.